Institutional Design Issues and Policy Challenges: Reflections From Former Chair of the Commerce Commission, Dr Mark Berry - Berry, Mark (Victoria University of Wellington Law Review, 2020)
I was asked by the Law and Economics Association of New Zealand to reflect tonight on my time as Chairman of the Commerce Commission (NZCC). I expect that the conference organisers may have wished that I revisited some of the key decisions during my ten year tenure. However, I fear that a retrospective of such cases would be dated, provide no new insights and would most likely be excruciatingly boring for this audience.